Optimizing the generation of polarization squeezed light in nonlinear optical fibers driven by femtosecond pulses - Andrianov, A. V.; Kalinin, Nikolay; Sorokin, A. A.; Anashkina, E. A.; Sánchez-Soto, L. L.; Corney, J. F.; Leuchs, Gerd (Optics Express, 2023)
Bright squeezed light can be generated in optical fibers utilizing the Kerr effect for ultrashort laser pulses. However, pulse propagation in a fiber is subject to nonconservative effects that deteriorate the squeezing. Here, we analyze two-mode polarization squeezing, which is SU(2)-invariant, robust against technical perturbations, and can be generated in a polarization-maintaining fiber. We perform a rigorous numerical optimization of the process and the pulse parameters using our advanced model of quantum pulse evolution in the fiber that includes various nonconservative effects and real fiber data. Numerical results are consistent with experimental results.
CRIS-Team Scopus Importer:2023-01-06